LO07: Procainamide for the acute management of atrial fibrillation and flutter in the emergency department: a systematic review. (May 2020) - Tran, F.; Junqueira, D.; Tan, M.; Rowe, B.
Abstract : Introduction: Management of acute atrial fibrillation or flutter (AFF) in the emergency department (ED) can be performed with chemical or electrical cardioversion. Procainamide is the most common chemical agent used in Canada; however, there is substantial practice variation. The objective of this systematic review was to provide comparative evidence on return to normal sinus rhythm (NSR) and adverse events to better support clinical decisions. Methods: Systematic search of five electronic databases and grey literature. Randomized controlled trials (RCTs) and prospective controlled cohort studies including adults (≥17 years) with recent-onset of AFF comparing intravenous procainamide with other cardioversion strategies (e.g., electrical cardioversion, placebo or other antiarrhythmic drugs) were eligible. Two independent reviewers performed study selection and data extraction. Relative risks (RR) with 95% confidence intervals (CIs) were calculated using a random-effects model. The protocol was registered with PROSPERO (CRD42019142080). Results: From 4060 potentially relevant citations, 7 studies were considered eligible and three RCTs and two cohort studies included in the analysis. Procainamide was less effective in promoting return to NSR at 1st attempt compared to other chemical (RR 0.76; 95% CI: 0.65 to 0.90) and electrical (RR 0.58; 95% CI: 0.53 to 0.64) options. Electrical cardioversion was more effective in restoring NSR compared to procainamide when used as 2nd attempt in one RCT (RR 0.46; 95% CI: 0.23 to 0.92). Pre-specified serious adverse events were assessed and reported by two studies showing that hypotension was more common in patients receiving procainamide in comparison with electrical cardioversion (RR 20.57; 95% CI: 1.59 to 265.63). Treatment discontinuation due to adverse events was infrequently reported with only two studies reporting that no patients withdrew from the study following treatment with procainamide. The remaining studies provided incomplete data reporting on adverse events. Conclusion: Shared decision-making for patients with acute AFF in the ED requires knowledge of the effectiveness and safety of comparative interventions. Overall, procainamide is less effective than other chemical options and electrical cardioversion strategies to restore NSR. Evidence shows that hypotension is a concern when procainamide is administered; however, the overall adverse events information provided from the studies is suboptimal.